2018
DOI: 10.1016/j.vaccine.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to accept a future influenza A(H7N9) vaccine in Beijing, China

Abstract: A great number of Beijing residents had doubts about the vaccine's effectiveness and were not concerned about disease risk, which were the factors affecting willingness to be vaccinated. Targeted education programs on disease risk as well as vaccine's effectiveness are needed to improve the willingness of vaccination for potential H7N9 pandemic preparedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Related study demonstrated the poultry industry loosed amounted to ¥7.75 billion (USD$1.24 billion) in 10 affected provinces and ¥3.68 billion (USD$0.59 billion) in eight non-affected adjacent provinces in only three months from March to May, 2013, [16] included cost of poultry slaughter, cost of closing LPMs, cost of live poultry sales and cost of market-stall leases. After the H7N9 outbreak in whole of China, reduced to 6% of the household had experience of purchasing poultry [26]. Meanwhile, the proportion of direct medical losses and DALYs losses in the estimate of H7N9 burden was small, but the medical costs per case were extremely high (mean cost for each patient was ¥10 117 (USD$1619) for mild patients, and ¥205 976 (USD$32 956) for severe cases with death).…”
Section: Discussionmentioning
confidence: 99%
“…Related study demonstrated the poultry industry loosed amounted to ¥7.75 billion (USD$1.24 billion) in 10 affected provinces and ¥3.68 billion (USD$0.59 billion) in eight non-affected adjacent provinces in only three months from March to May, 2013, [16] included cost of poultry slaughter, cost of closing LPMs, cost of live poultry sales and cost of market-stall leases. After the H7N9 outbreak in whole of China, reduced to 6% of the household had experience of purchasing poultry [26]. Meanwhile, the proportion of direct medical losses and DALYs losses in the estimate of H7N9 burden was small, but the medical costs per case were extremely high (mean cost for each patient was ¥10 117 (USD$1619) for mild patients, and ¥205 976 (USD$32 956) for severe cases with death).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 As of 17th October 2020, the virus has rapidly spread in the Kingdom, causing a total of 341,495 laboratory-confirmed cases with 5144 deaths. 7 A vaccine is considered to be the most awaiting intervention 2,4,7 and hundreds of global R&D institutions engaged in unprecedented speed to develop the vaccine [7][8][9][10][11] However, public perception towards COVID-19 vaccine uptake is not available. Numerous studies have shown several factors responsible for vaccine acceptancy when a new vaccine is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…18 In Beijing, China, 59.5% of the study participants who had heard of H7N9 were willing to accept a future influenza A (H7N9) Vaccine. 8 Vaccine acceptance and demand are complex in nature and context-specific, varying across time, place, and perceived behavioral nature of the community. [9][10][11][12][13][14][15] A study in Ireland showed that health care workers avoided seasonal influenza vaccination due to their misconception, efficacy, and trust in the vaccine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An o cial from China's health ministry said on television on 22 August 2020 [30] that This mirrors the vaccination strategy used in response to the 2009 H1N1 pandemic in China, in which priority groups (e.g., older individuals, students, civil servants, etc.) received the vaccine followed by other groups [32]. However, according to modeling results, the priority of targeted vaccination would depend on the effectiveness of future COVID-19 vaccines [23].…”
Section: Discussionmentioning
confidence: 99%